District-Wise Distribution and Trends of Cancer Incidence in Nepal: A Five-Year Analysis (2016–2020) - Subedi, Krishna Prasad; Poudel, Rishiram; Poudel, Shivaji; Gautam, Dej Kumar; Bhatta, Pramod; Rana, Hari Bahadur (Journal of Manmohan Memorial Institute of Health Sciences, 2025)
Introduction: Cancer is an increasing public health concern in Nepal. This study utilizes secondary data collected from B.P. Koirala Memorial Cancer Hospital (BPKMCH), the national authority responsible for data collection under the National Cancer Registry. Method: A total of 62,492 new cancer cases were diagnosed and treated between January 1, 2016, and December 31, 2020. Key variables such as name, age, sex, address, and cancer site were recorded to determine the distribution of cancer across the country. These variables were verified and categorized based on topographical regions where patients reported. Cancer cases were coded according to the International Classification of Diseases for Oncology (ICD-O-10, Third Edition), and data analysis was performed using SPSS version 29.0. Results: The highest number of cancer cases was reported from Kathmandu (12.33%), followed by Jhapa (4.10%) and Morang (3.74%) districts. Conclusion: The incidence of cancer showed an increasing trend over the study period. To reduce the cancer burden in Nepal, well-organized awareness campaigns, HPV vaccination, and regular screening programs are strongly recommended.